Astrocytic and Oligodendrocytic P2X7 Receptors Determine Neuronal Functions in the CNS - Zhao, Ya-Fei; Tang, Yong; Illes, Peter (Frontiers in Molecular Neuroscience, 2021)
P2X7 receptors are members of the ATP-gated cationic channel family with a preferential localization at the microglial cells, the resident macrophages of the brain. However, these receptors are also present at neuroglia (astrocytes, oligodendrocytes) although at a considerably lower density. They mediate necrosis/apoptosis by the release of pro-inflammatory cytokines/chemokines, reactive oxygen species (ROS) as well as the excitotoxic (glio)transmitters glutamate and ATP. Besides mediating cell damage i.e., superimposed upon chronic neurodegenerative processes in Alzheimer’s Disease, Parkinson’s Disease, multiple sclerosis, and amyotrophic lateral sclerosis, they may also participate in neuroglial signaling to neurons under conditions of high ATP concentrations during any other form of neuroinflammation/neurodegeneration. It is a pertinent open question whether P2X7Rs are localized on neurons, or whether only neuroglia/microglia possess this receptor-type causing indirect effects by releasing the above-mentioned signaling molecules. We suggest as based on molecular biology and functional evidence that neurons are devoid of P2X7Rs although the existence of neuronal P2X7Rs cannot be excluded with absolute certainty.